Study on the deformation mechanics of hard brittle coatings on ductile substrates using in-situ tensile testing and cohesive zone FEM modeling - Rehman, Hamad Ur; Ahmed, Furqan; Schmid, Christoph; Schaufler, Jens; Durst, Karsten (Surface & Coatings Technology, 2012)
In the present work, the mechanics of the stress transfer from a ductile substrate to a brittle coating and the failure of coating segments by normal cracking and delamination are studied using in-situ tensile testing and cohesive zone finite element modeling. The in-situ tensile tests were performed in a scanning electron microscope (SEM) on a diamond coated Ti-substrate and hydrogenated amorphous carbon (a-C:H) coatings on two different steel substrates, with different work hardening behavior. These brittle coatings form cracked coating segments during the in-situ tensile test. The stress transfer from the substrate to the coating segments is dependent on the elastic and elastic/plastic properties of coating and substrate. Furthermore, the segmentation of the coating together with the delamination depends strongly on the film and substrate properties. Using cohesive zone finite element modeling, the influence of substrate and coating properties on the stress transfer, segmentation of the films and on the delamination is discussed. It was found that the saturation in spacing of the cracked coating segments is either cause by a localization of the plastic strain in the substrate or by a delamination of the coating segments. Delamination only occurs, when the flow stress of the substrate is about √3 times larger than the interfacial shear strength.
WW1::945